Growth of Assam Gramin Vikash Bank in Credit Deployment: An Analysis - Kashyap, Pinkumoni; Adhikari , Kingshuk; Dey, Nikhil Bhusan (Gyan Management Journal, 2015)
This paper seeks to examine the growth of outstanding advances of Assam Gramin Vikash Bank for a  period of nine years from 2006 to 2014. In order to analyze growth, total advances, advances to priority  sector, non priority sector, Agriculture & Allied, SSI/MSME, Service & Other and Housing have been  considered. The results have been derived from the use of statistical tools like Yo Y Growth Rate,  Compound Annual Growth Rate (CAGR), t-test, Kolmogorov-Smirnov Test & Shapiro-Wilk Test and  ANOVA. The study reveals that Assam Gram in Vikash Bank has made considerable growth in terms of  credit deployment.
Keywords: Advance; Growth; credit deployment performance; total advances